Solve Using the Square Root Property x^2-5x-9=0

Math
x2-5x-9=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=-5, and c=-9 into the quadratic formula and solve for x.
5±(-5)2-4⋅(1⋅-9)2⋅1
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -5 to the power of 2.
x=5±25-4⋅(1⋅-9)2⋅1
Multiply -9 by 1.
x=5±25-4⋅-92⋅1
Multiply -4 by -9.
x=5±25+362⋅1
Add 25 and 36.
x=5±612⋅1
x=5±612⋅1
Multiply 2 by 1.
x=5±612
x=5±612
Simplify the expression to solve for the + portion of the ±.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -5 to the power of 2.
x=5±25-4⋅(1⋅-9)2⋅1
Multiply -9 by 1.
x=5±25-4⋅-92⋅1
Multiply -4 by -9.
x=5±25+362⋅1
Add 25 and 36.
x=5±612⋅1
x=5±612⋅1
Multiply 2 by 1.
x=5±612
Change the ± to +.
x=5+612
x=5+612
Simplify the expression to solve for the – portion of the ±.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -5 to the power of 2.
x=5±25-4⋅(1⋅-9)2⋅1
Multiply -9 by 1.
x=5±25-4⋅-92⋅1
Multiply -4 by -9.
x=5±25+362⋅1
Add 25 and 36.
x=5±612⋅1
x=5±612⋅1
Multiply 2 by 1.
x=5±612
Change the ± to -.
x=5-612
x=5-612
The final answer is the combination of both solutions.
x=5+612,5-612
The result can be shown in multiple forms.
Exact Form:
x=5+612,5-612
Decimal Form:
x=6.40512483…,-1.40512483…
Solve Using the Square Root Property x^2-5x-9=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top